Composite oxide, method for preparing composite oxide, hydrogenation catalyst and use thereof
By using a composite oxide catalyst composed of aluminum oxide and titanium oxide, the problem of insufficient low-temperature activity and selectivity of the catalyst in the prior art is solved, and efficient and stable selective hydrogenation of allylic compounds is achieved, thereby improving the extraction efficiency and economicality of the adiene.
Patent Information
- Application Number
- JP2024556473
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-24
- Filing Date
- 2022-11-04
- Publication Date
- 2025-04-15
AI Technical Summary
In the prior art, when selectively hydrogenating allylic compounds, the catalyst has low low temperature activity and selectivity, and is easily poisoned by pollutants, has a short lifespan, resulting in poor productivity and economicality.
A composite oxide composed of aluminum oxide and titanium oxide is used as a catalyst support to obtain a catalyst with a coronal 3D layered structure through a specific preparation method, which improves its surface area and active sites, and enhances the selectivity and stability of allyl compounds.
A catalyst with high high and low temperature activity and selectivity has been achieved, which significantly improves the anti-pollution poisoning ability and life of the catalyst, reduces production costs, and improves the extraction efficiency of the adiene.
Smart Images

Figure 2025510789000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite oxide, a preparation method for the composite oxide, a hydrogenation catalyst and its application. Specifically, the hydrogenation catalyst can be used to remove alkynes in a C4 fraction through hydrogenation and increase the production of butadiene. [Background technology]
[0002] C4 fraction refers to a mixture of various alkanes, olefins, diolefins and alkynes containing four carbon atoms. C4 fraction is mainly derived from refinery gas produced in oil refining process and by-products during cracking of petroleum hydrocarbons into ethylene. Cracked C4 streams may contain saturated and unsaturated hydrocarbons such as n-butane, isobutane, 1-butene, trans-2-butene, cis-2-butene, isobutene, 1,2-butadiene, 1,3-butadiene, methyl acetylene, ethyl acetylene, vinyl acetylene, etc., and are mainly used in industry to produce 1,3-butadiene, isobutylene and 1-butene.
[0003] Cracked C4 fraction, a by-product of high-temperature cracking of hydrocarbons to produce ethylene, usually contains 40-60 mass% butadiene. Butadiene is an important monomer in the synthetic rubber industry. Solvent extraction methods such as acetonitrile method, N-methylpyrrolidone method and dimethylformamide method are usually used to extract butadiene from cracked C4 fraction. At present, these methods can basically meet the requirements for butadiene purity.
[0004] Due to the influence of factors such as the severity of cracking and cracking technology, the alkyne content in the cracked carbon 4 fraction gradually increases, resulting in an increase in the loss of butadiene and an increase in energy consumption during the extraction process. At the same time, with the progress of organic synthesis industrial technology, the regulation of the alkyne content in butadiene becomes stricter. These factors have led to poor economics of butadiene extraction equipment. In the butadiene extraction process, selective hydrogenation of alkynes and partial recovery of butadiene can not only achieve the purpose of turning waste into treasure, but also play an important role in reducing the emission of alkynes and preventing environmental pollution.
[0005] Currently, alkynes in mixed hydrocarbon fractions with carbon numbers of 4 can be removed by selective hydrogenation using a catalyst. The catalysts used are mainly precious metal catalysts such as palladium, platinum, and silver, with non-precious metal catalysts such as copper and nickel tending to be used secondarily.
[0006] In the selective hydrogenation of alkynes in a hydrocarbon stream, the catalyst and reaction conditions selected vary depending on the composition of the feedstock and the target product. In addition to high hydrogenation activity, a good selective hydrogenation catalyst must have good stability, i.e., the ability to resist impurities and colloids to extend the catalyst's life. Therefore, the support is required to have lower acidity, smaller specific surface area, and larger pore size. In addition, the addition of some additives during the preparation of the catalyst can also extend the catalyst's service life.
[0007] As the noble metal catalyst, a palladium catalyst supported on a carrier (usually alumina) is commonly used, and other cocatalyst components, such as gold, silver, chromium, copper, iron, rhodium, lithium, potassium, lead or zinc, are added. Noble metal catalysts have excellent low-temperature activity and mild reaction conditions, but they have the disadvantages of easy loss of active components, high cost, difficulty in regeneration, and slightly poor hydrogenation selectivity. Non-noble metal catalysts need to be reacted at high temperatures and have harsh hydrogenation conditions, but they are easy to prepare, easy to repeatedly regenerate, and relatively inexpensive, so they are worth researching and developing to some extent. During this kind of hydrogenation reaction, the semi-hydrogenated free radicals adsorbed on the catalyst react with the adjacent alkynes or dienes to form viscous polymers (commonly known as green oils) mainly composed of compounds with C6 or more. The polymer covers the catalyst surface and blocks the micropores on the catalyst surface, which may reduce the activity of the catalyst and affect the service life of the catalyst. In particular, conjugated dienes (for example, 1,3-butadiene) undergo polymerization reactions easily, causing the catalyst to become deactivated in a short period of time, and therefore necessitating frequent regeneration in order to reuse the catalyst.
[0008] In application research in the field of selective hydrogenation of C4 alkynes, it has been found that nickel-based selective hydrogenation catalysts are safer and more efficient for raw materials containing high concentrations of alkynes, but nickel-based selective hydrogenation catalysts are less active and selective than precious metal palladium-based catalysts, so their application is limited. Therefore, for non-precious metal catalysts for selective hydrogenation of alkynes, it is necessary to further improve the activity and selectivity of the catalyst, research into countermeasures to the green oil problem when using the catalyst, and extend the service life of the catalyst. For the selective hydrogenation reaction of alkynes, the use of non-precious metal hydrogenation catalysts can improve the impurity poisoning resistance and stability of the catalyst, which is economically valuable.
[0009] According to research in the field of photocatalysis, the structure and shape of catalytic materials based on TiO2 greatly affect the light absorption efficiency of the material. Coral reefs have excellent light absorption and reflection structures, provide a three-dimensional (3D) environment for many plants and animals on the seafloor, and can absorb small particles, supporting the lives of about a quarter of known marine organisms. The coral-like 3D layer structure has a larger specific surface area than other structures, resulting in more active sites, stronger light-capturing ability, and better photocatalytic performance. By using a specific catalytic material with a morphology similar to that of a coral reef, the performance of TiO2-supported catalysts can be improved. Summary of the Invention
[0010] In view of the shortcomings of the prior art, the object of the present invention is to provide a non-precious metal selective hydrogenation catalyst with high low-temperature activity, high selectivity and high stability.Compared with the precious metal selective hydrogenation catalyst for removing alkynes, the catalyst disclosed herein can save more than 80% of investment cost, and has excellent resistance to impurity poisoning and raw material adaptability.
[0011] In a first aspect, the present invention provides a composite oxide comprising aluminum oxide and titanium dioxide, the composite oxide comprising Xm 2 The composite oxide has a specific surface area expressed as 1 / g and an average pore size expressed as Y nm, the ratio of X to Y being 5 to 30, and in the composite oxide, titanium dioxide in the anatase crystal phase accounts for 95% by weight to 100% by weight of the entire titanium dioxide. Preferably, the ratio of X to Y is 5 to 15. More preferably, the ratio of X to Y is 5 to 10. Preferably, in the composite oxide, titanium dioxide in the anatase crystal phase accounts for 96% by weight to 100% by weight of the entire titanium dioxide. Preferably, in the composite oxide, titanium dioxide in the anatase crystal phase accounts for 97% by weight to 100% by weight of the entire titanium dioxide. Preferably, in the composite oxide, titanium dioxide in the anatase crystal phase accounts for 98% by weight to 100% by weight of the entire titanium dioxide. Preferably, in the composite oxide, titanium dioxide in the anatase crystal phase accounts for 99% by weight to 100% by weight of the entire titanium dioxide.
[0012] In the present invention, the proportion of titanium dioxide in the anatase crystal phase in the entire titanium dioxide can be measured by X-ray diffraction analysis.
[0013] In the present invention, the specific surface area of the composite oxide can be measured by the BET method.
[0014] In the present invention, the average pore size of the composite oxide can be measured by a nitrogen adsorption isotherm method.
[0015] In some embodiments of the present invention, the diffraction peak area representing the anatase titanium dioxide crystal structure as measured by X-ray diffraction analysis accounts for 95% to 100% by weight of the diffraction peak areas of all titanium dioxide crystal structures.
[0016] In some embodiments of the present invention, the diffraction peak area representing the anatase titanium dioxide crystal structure as measured by X-ray diffraction analysis accounts for 96% to 100% by weight of the diffraction peak areas of all titanium dioxide crystal structures.
[0017] In some embodiments of the present invention, the diffraction peak area representing the anatase titanium dioxide crystal structure as measured by X-ray diffraction analysis accounts for 97% to 100% by weight of the diffraction peak areas of all titanium dioxide crystal structures.
[0018] In some embodiments of the present invention, the diffraction peak area representing the anatase titanium dioxide crystal structure as measured by X-ray diffraction analysis accounts for 98% to 100% by weight of the diffraction peak areas of all titanium dioxide crystal structures.
[0019] In some embodiments of the invention, the complex oxide has a pore volume of Z mL / g, measured using a P / Po single point desorption curve, and the ratio of X to Z is 220 to 400, preferably 250 to 350. In some embodiments, the ratio of X to Z is 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, or 350, or a range between any two of these points.
[0020] In some embodiments of the invention, X is between 90 and 150. In some embodiments, X is 90, 100, 110, 120, 130, 140, or 150, or a range between any two of these points.
[0021] In some embodiments of the invention, Y is 9 to 20, preferably 12 to 16. In some embodiments, Y is 12, 13, 14, 15, or 16, or a range between any two of these points.
[0022] In some embodiments of the present invention, the proportion of pores having a pore diameter in the range of 10 to 20 nm in the total pores in the composite oxide is at least 85% by volume.
[0023] In some embodiments of the invention, Z is 0.3 to 0.5, preferably 0.3 to 0.4, hi some embodiments, Z is 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, or 0.40, or a range between any two of these points.
[0024] In some embodiments of the present invention, the composite oxide comprises 5% to 21% by weight of titanium dioxide based on the total weight of the composite oxide, hi some embodiments, the composite oxide comprises 5%, 6%, 8%, 10%, 12%, 15%, 18%, 20%, or 21% by weight of titanium dioxide, or any amount ranging between any two of these points.
[0025] In some embodiments of the present invention, the composite oxide comprises 79% to 95% by weight of aluminum oxide, based on the total weight of the composite oxide.
[0026] In some embodiments of the present invention, the composite oxide has a 3D layer structure like a coral bush, which has a larger specific surface area, resulting in more active sites and stronger light-harvesting ability.
[0027] In a second aspect, the present invention provides a method for preparing a composite oxide, by which an alumina-titanium dioxide composite oxide having a 3D microscopic morphology of a coral thicket can be obtained. The preparation method of the present invention includes: (I) dissolving a soluble aluminum source in water to form an aluminum source solution, dissolving a titanium source in an acid solution to form a titanium source solution, and mixing an ammonium salt and an alkali solution to form a mixed alkali solution; (II) (a) adding the titanium source solution and the mixed alkali solution to the aluminum source solution and maintaining the resulting mixed solution at a first pH value for a first period of time; (b) adding an additional amount of the mixed alkali solution to the mixed solution and maintaining the resulting mixed solution at a second pH value for a second period of time; (c) adding an additional amount of the titanium source solution to the mixed solution and maintaining the resulting mixed solution at a third pH value for a third period of time; (III) after step (II)(c), increasing the temperature of the mixed solution and maintaining it at that temperature for a fourth period of time to obtain a precipitate; and (IV) drying and calcining the precipitate to obtain a composite oxide comprising alumina and titanium dioxide, preferably with washing and filtering prior to drying (to remove unwanted impurities).
[0028] The composite oxide thus obtained has the compositional and structural characteristics described in the first aspect of the present invention.
[0029] In some embodiments of the method of the present invention, in step (II), the first pH value is less than 5, preferably in the range of 3 to 4. In some embodiments of the method of the present invention, in step (II), the second pH value is greater than 8.5, preferably in the range of 9 to 10. In some embodiments of the method of the present invention, in step (II), the third pH value is greater than 7 and less than 9, preferably in the range of 7.5 to 8.5.
[0030] In some embodiments of the method of the present invention, in step (II), each of the first, second and third periods is from 5 to 20 minutes, preferably from 10 to 15 minutes.
[0031] In some embodiments of the method of the present invention, in step (III), the fourth period of time is from 20 to 60 minutes.
[0032] In some embodiments of the process of the present invention, in step (II), the operating temperature is from 25°C to 60°C, preferably from 50°C to 60°C.
[0033] In some embodiments of the method of the present invention, in step (III), the temperature is increased to 80° C. to 150° C., preferably 80° C. to 100° C. In some embodiments, in step (III), the temperature is increased to 80° C., 85° C., 90° C., 92° C., or 95° C.
[0034] In some embodiments of the method of the present invention, in step (IV), the drying temperature is in the range of 110° C. to 130° C. The drying time is 4 hours to 12 hours, preferably 6 hours to 10 hours.
[0035] In some embodiments of the method of the present invention, in step (IV), the calcination temperature is in the range of 800° C. to 1000° C. In some embodiments, in step (IV), the calcination temperature is 800° C., 850° C., 900° C., or 950° C., or in a range between any two of these points. The calcination time is 4 hours to 12 hours, preferably 5 hours to 8 hours.
[0036] In some embodiments of the method of the present invention, the aluminum source solution has an aluminum concentration of 0.5 to 2.5 mol / L. The aluminum source is one or more of soluble aluminum salts, such as aluminum sulfate, aluminum chloride, aluminum nitrate, and organoaluminum salts, such as aluminum isopropoxide, aluminum sec-butoxide, aluminum monoacetate, and aluminum diacetate.
[0037] In some embodiments of the method of the present invention, the titanium source solution has a titanium concentration of 0.2 to 1.2 mol / L. The titanium source is a soluble titanium source and can be selected from titanium salts such as titanium acetate, titanium chloride, titanium sulfate and titanium nitrate, and titanate esters such as tetraethyl titanate, tetra-n-propyl titanate, tetraisopropyl titanate and tetrabutyl titanate.
[0038] In some embodiments of the method of the present invention, the mixed alkaline solution has an ammonium salt concentration of 0.1 to 0.3 mol / L. The ammonium salt may be one or more selected from ammonium bicarbonate, ammonium carbonate, and organic ammonium salts.
[0039] In some embodiments of the method of the present invention, the alkaline liquid has an alkaline concentration of 0.2 to 0.4 mol / L. The alkaline liquid may be one or more selected from ammonia, sodium hydroxide, potassium hydroxide, and organic bases such as triethylamine, N,N-dimethylaniline, pyridine, and quinoline.
[0040] In some embodiments of the methods of the present invention, the acid solution may be one or more selected from sulfuric acid, nitric acid, hydrochloric acid, and organic acids such as formic acid, acetic acid, citric acid, and oxalic acid.
[0041] In some embodiments of the process of the present invention, the ratios of reactants charged in steps (II)(a), (II)(b) and (II)(c) are as follows:
[0042] The ratio of the titanium source solution charged in step (II)(a) and (II)(c) may be in the range of 1:4 to 2:3. Alternatively, the amount of titanium source solution charged in step (II)(a) accounts for 20 to 40 volume % of the total amount of titanium source solution charged in the method, and the amount of titanium source solution charged in step (II)(c) accounts for 60 to 80 volume % of the total amount of titanium source solution charged in the method.
[0043] The ratio of the mixed alkaline solutions filled in steps (II)(a) and (II)(b) may be in the range of 2:1 to 1:2, or 1.5:1 to 1:1. Alternatively, of the total amount of the mixed alkaline solutions filled in steps (II)(a) and (II)(b), the amount of the mixed alkaline solution filled in step (II)(a) accounts for 33 to 67% by volume, preferably 50 to 60% by volume, and the amount of the mixed alkaline solution filled in step (II)(b) accounts for 33 to 67% by volume, preferably 40 to 50% by volume.
[0044] In some embodiments of the method of the present invention, in step (IV), the precipitate washing step includes washing with deionized water until acid ions are no longer detectable, the drying temperature is 100°C to 120°C, the drying time is 4°C to 12 hours, and the calcination temperature is 800°C to 1000°C.
[0045] The composite oxide prepared by the method provided by the present invention contains 5% by weight to 21% by weight of titanium dioxide, and titanium dioxide and alumina are uniformly mixed. Furthermore, the present inventors have surprisingly found that the composite oxide has a surface micromorphology of a coral bush-like 3D layer structure. The coral bush-like 3D layer structure can provide the composite oxide with a larger specific surface area, thereby having more active sites and stronger electron capture ability, which promotes the co-catalytic effect of TiO2 as an electron promoter and helps to improve the overall performance of the catalyst, including activity and selectivity.
[0046] Furthermore, it is generally believed that during the calcination of TiO2, rutile is formed from a calcination temperature of 500°C, and most of the crystalline phase of TiO2 changes from anatase phase to rutile phase at a calcination temperature of more than 700°C. However, after the composite oxide prepared by the method provided herein is calcined at a high temperature of 800°C or more, X-ray diffraction analysis has revealed that anatase titanium dioxide accounts for 95-100% by weight of the total crystalline phase of TiO2, contrary to common sense. TiO2 present in the form of anatase in the composite oxide has an electron induction effect, which can effectively induce a decrease in the electron cloud density of the active metal Ni in the prepared catalyst (compared to the rutile phase produced by high-temperature calcination), thereby improving the adsorption ability for alkynes in the reaction raw material, and improving the selective hydrogenation activity and selectivity of the catalyst.
[0047] In a third aspect, the present invention further provides uses of the complex oxide, including the use of the complex oxide of the first aspect of the present invention or the complex oxide prepared by the method of the second aspect as a catalyst support.
[0048] According to the present invention, the type of catalyst is not particularly limited.
[0049] In some embodiments, the present invention provides a hydrogenation catalyst comprising a complex oxide of the first aspect of the present invention or a complex oxide prepared by the method of the second aspect of the present invention, and an active component such as palladium, nickel, iron or cobalt.
[0050] In some embodiments of the hydrogenation catalyst of the present invention, the hydrogenation metal is nickel. In some embodiments, the hydrogenation catalyst may have a nickel content of 8 to 25 wt%, preferably 12 to 20 wt%. In other embodiments, the hydrogenation catalyst comprises palladium, which may be present in an amount of 0.1 to 2 wt%, for example 0.15 to 1.5 wt%.
[0051] In a fourth aspect, the present invention further provides a process for selective hydrogenation of alkynes comprising subjecting a distillate oil to selective hydrogenation of alkynes in the presence of a hydrogenation catalyst as described in the third aspect to increase the production of butadiene, the distillate oil comprising a C4 distillate oil, preferably a high alkyne tail gas produced as a by-product in a butadiene extraction unit.
[0052] Furthermore, in the process for selective hydrogenation of alkynes, the reaction temperature is 20°C-40°C, the molar ratio of hydrogen to alkyne is 1:1-2.5:1, the pressure is 0.5MPa-0.8MPa, and the circulation ratio is 10:1-30:1.
[0053] The catalyst provided by the present invention exhibits a relatively high vinylacetylene conversion and a high selectivity for 1,3-butadiene in the selective hydrogenation of alkynes. [Brief description of the drawings]
[0054] [Figure 1] 1 shows the 3D coral bush-like microscopic morphology of the alumina-titanium dioxide composite oxide prepared in Example 1. [Diagram 2] 1 shows an XRD pattern of the alumina-titanium dioxide composite oxide prepared in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0055] [Example] The present invention will be described in detail below with reference to examples for easier understanding of the present invention. These examples are for illustrative purposes only and are not intended to limit the scope of the present invention.
[0056] Unless otherwise specified, the raw materials or components used in the present invention are either commercially available or can be prepared by conventional methods.
[0057] To determine the specific surface area and pore structure of the complex oxides, an ASAP 2020 model adsorption apparatus (N2 adsorption and desorption method) was used, available from Mike Instrument Company, USA. Prior to the measurements, the complex oxide samples were degassed at 623 K for 4 h and nitrogen was adsorbed at liquid nitrogen temperature. AMSM software was used to process the sample data, and the Brunauer-Emmet-Teller (BET) method was used to obtain the specific surface area of the samples. The Barrett-Joyner-Halenda (BJH) method was used to obtain the average pore diameter based on the nitrogen adsorption isotherm, and the P / Po single-point desorption curve was used to obtain the pore volume.
[0058] The morphology of the complex oxides was observed using a scanning electron microscope, model QUANTA 200, available from FEI Company.
[0059] The crystalline phase structure of the complex oxides was characterized using an EMPYREAN X-ray diffractometer, available from PANalytical BV, The Netherlands. Cu Kα was used as the radiation source, the X-ray tube voltage was 40 kV, the phototube current was 40 mA, the slit width was 10 mm, the scan range was 5–90°, and the scan speed was 0.013° / s.
[0060] [Example 1] 328.02 g of Al2(SO4)3 was dissolved in deionized water to prepare 1000 mL of aluminum sulfate solution. 21.14 g of TiO(OH)2 was dissolved in 16 mL of 98 wt% sulfuric acid and deionized water was added to prepare 500 mL of metatitanic acid solution in dilute sulfuric acid. 18 g of NH4HCO3 was dissolved in 600 mL of deionized water to prepare ammonium bicarbonate solution, then 250 mL of 27 wt% ammonia water was added, the resulting mixed solution was stirred to mix uniformly, and then supplemented with deionized water to prepare 1000 mL of mixed alkaline solution.
[0061] At normal pressure and at a temperature of 55°C, 230mL of the metatitanic acid solution in dilute sulfuric acid and 360mL of the mixed alkali solution were added in parallel with strong stirring to 1000mL of the prepared aluminum sulfate solution, and the pH value of the resulting mixed solution was maintained at 3-4 for 15 minutes. Then, an additional 320mL of the mixed alkali solution was added to bring the pH value to 9-10, and the reaction mixture was maintained at that pH value for 15 minutes. Then, the remaining metatitanic acid solution in dilute sulfuric acid was added to bring the pH value to 7.5-8.5, and the reaction mixture was maintained at that pH value for 6-10 minutes. Next, the temperature was increased to 92°C and maintained for 20 minutes, and then the reaction mixture was filtered. The filter cake was repeatedly washed five times with 20 times the amount of deionized water, and the washed filter cake was dried at 110°C for 6 hours and calcined at 850°C for 5 hours. 114.3g of composite oxide was obtained, with a TiO2 content of 15.0 wt%.
[0062] From the SEM in FIG. 1, it can be seen that the composite oxide exhibits a surface micromorphology of a 3D layered structure like a coral bush. FIG. 2 is the XRD pattern of the alumina-titanium dioxide composite oxide prepared in Example 1. For titanium dioxide, the characteristic diffraction peak of anatase appears only at 2θ=25.4°, and no diffraction peaks of other crystal phases appear at other positions, indicating that all of the TiO2 components in the composite oxide exist as anatase crystal phase. In other words, titanium dioxide in the anatase crystal phase accounts for 100% by weight of the entire titanium dioxide.
[0063] [Example 2] 256.04 g of Al2(SO4)3 was dissolved in deionized water to prepare 1000 mL of aluminum sulfate solution. 32.15 g of Ti(SO4)2 was dissolved in deionized water and 5 mL of concentrated sulfuric acid (98%) was added to prepare 500 mL of titanium sulfate solution in dilute sulfuric acid. 18 g of NH4HCO3 was dissolved in 600 mL of deionized water to prepare ammonium bicarbonate solution, then 250 mL of 27 wt% ammonia water was added, the resulting mixed solution was stirred to mix uniformly, and then supplemented with deionized water to prepare 1000 mL of mixed alkaline solution.
[0064] At normal pressure and at a temperature of 60°C, 280 mL of titanium sulfate solution in dilute sulfuric acid and 320 mL of mixed alkali solution were added in parallel to 1000 mL of aluminum sulfate solution under strong stirring, and the pH value of the resulting mixed solution was maintained at 3-4 for 15 minutes. Then, an additional 240 mL of mixed alkali solution was added to bring the pH value to 9-10, and the reaction mixture was maintained at that pH value for 15 minutes. Then, the remaining titanium sulfate solution in dilute sulfuric acid was added to bring the pH value to 7.5-8.5. Next, the temperature was raised to 85°C and maintained for 40 minutes, and then the reaction mixture was filtered. The filter cake was repeatedly washed five times with 20 times the amount of deionized water, and the washed filter cake was dried at 110°C for 6 hours and calcined at 950°C for 5 hours. 86.8 g of alumina-titanium dioxide composite oxide was obtained, with a TiO2 content of 12.3 wt%.
[0065] [Example 3] The procedure for preparing titanium dioxide-alumina composite oxide described in Example 1 was repeated, except that 379.79 g of Al(NO3)3 was dissolved in deionized water to prepare 1000 mL of aluminum nitrate solution, and 25.99 g of Ti(OCH2CH3)4 was dissolved in absolute ethanol to prepare 500 mL of tetraethyl titanate solution in ethanol. Finally, an alumina-titanium dioxide composite oxide with a TiO2 content of 9.1% was obtained.
[0066] [Example 4] The procedure for preparing titanium dioxide-alumina composite oxide described in Example 1 was repeated, except that 396.92 g of Al(NO3)3 was dissolved in deionized water to prepare 1000 mL of aluminum nitrate solution, and 6.13 g of TiO(OH)2 was dissolved in sulfuric acid and deionized water was added to prepare 500 mL of metatitanic acid solution in dilute sulfuric acid. Finally, an alumina-titanium dioxide composite oxide with a TiO2 content of 5.0% was obtained.
[0067] [Example 5] The procedure for preparing titanium dioxide-alumina composite oxide described in Example 1 was repeated, except that 396.92 g of Al(NO3)3 was dissolved in deionized water to prepare 1000 mL of aluminum nitrate solution, 6.13 g of TiO(OH)2 was dissolved in sulfuric acid and deionized water was added to prepare 500 mL of metatitanic acid solution in dilute sulfuric acid, and the temperature for calcining the filter cake was 800° C. Finally, an alumina-titanium dioxide composite oxide with a TiO2 content of 5.0% was obtained.
[0068] [Example 6] The procedure for preparing titanium dioxide-alumina composite oxide described in Example 1 was repeated, except that 374.13 g of AlCl3·6H2O was dissolved in deionized water to prepare 1000 mL of aluminum chloride solution, and 59.99 g of Ti(OCH2CH3)4 was dissolved in absolute ethanol to prepare 500 mL of tetraethyl titanate solution in ethanol. Finally, an alumina-titanium dioxide composite oxide with a TiO2 content of 21.0% was obtained.
[0069] Scanning electron microscope and XRD tests showed that the composite oxides prepared in Examples 2-6 were similar to those in Example 1, exhibiting a surface micromorphology of a coral bush-like 3D layered structure, and the TiO2 components in the composite oxides all existed as anatase crystalline phase.
[0070] [Comparative Example 1] 268.46 g of Al2(SO4)3 was dissolved in deionized water to prepare 1000 mL of aluminum sulfate solution. 24.5 g of TiO(OH)2 was dissolved in sulfuric acid and deionized water was added to prepare 1000 mL of metatitanic acid solution in dilute sulfuric acid. 18 g of NH4HCO3 was dissolved in 600 mL of deionized water to prepare ammonium bicarbonate aqueous solution, and 250 mL of 24-28 wt% ammonia water was added, the resulting mixed solution was stirred to mix uniformly, and supplemented with deionized water to prepare 1000 mL of mixed alkaline solution.
[0071] Under normal pressure and temperature conditions of 70-75°C, the above three solutions, namely, the aluminum sulfate solution in deionized water, the metatitanic acid solution in dilute sulfuric acid, and the mixed alkaline solution, were mixed in parallel flow to carry out coprecipitation. The flow rate of the mixed alkaline solution was controlled so that the pH value of the precipitation reactant was maintained in the range of 5.0-6.0 for 8 minutes, and then the flow rate of the mixed alkaline solution was increased so that the pH value of the mixed solution was maintained in the range of 8.5-9.5 for 8 minutes. Next, the flow rate of the mixed alkaline solution was decreased so that the pH value of the mixed solution was maintained in the range of 5.0-6.0 for 8 minutes, and then the flow rate of the mixed alkaline solution was increased so that the pH value of the precipitation reactant was maintained in the range of 8.5-9.5. This operation was repeated until the drop of solutions A1 and B1 was completed. The reaction solution was left to stand at 70°C for 30 minutes, then filtered, and the filter cake was washed with 15 times the volume of deionized water for 30 minutes, filtered again, and washed again. This process was repeated four times, and finally the filter cake was dried at 100-120 °C for 8-12 h and calcined at 950 °C for 5 h to obtain titanium dioxide-alumina composite. The structure and performance results of the composite are shown in Table 1.
[0072] [Comparative Example 2] 401.88 g of analytically pure AlCl3·6H2O was dissolved in 1000 ml of deionized water to prepare solution A1. 43.25 g of chemically pure Ti(OCH2CH3)4 was dissolved in 500 ml of benzene (benzene content is 99.8 wt%) to prepare solution B1. 18 g of analytically pure NH4HCO3 was dissolved in 600 ml of deionized water, 250 ml of 24-28 wt% ammonia water was added thereto, the resulting mixed solution was stirred to mix uniformly, and supplemented with deionized water to prepare 1000 mL of solution C1.
[0073] Under normal pressure and temperature conditions of 70-75°C, the three solutions A1, B1 and C1 were mixed in parallel to carry out coprecipitation. The flow rate of solution C1 was controlled so that the pH value of the precipitation reactant was maintained in the range of 5.0-6.0 for 8 minutes, and then the flow rate of solution C1 was increased so that the pH value of the mixed solution was maintained in the range of 8.5-9.5 for 8 minutes. Next, the flow rate of solution C1 was decreased so that the pH value of the mixed solution was maintained in the range of 5.0-6.0 for 8 minutes, and then the flow rate of solution C1 was increased so that the pH value of the precipitation reactant was maintained in the range of 8.5-9.5. This operation was repeated until the drop of solutions A1 and B1 was completed. The reaction solution was left to stand at 70°C for 30 minutes, then filtered, and the filter cake was washed with 15 times the volume of deionized water for 30 minutes, filtered again, and washed again. This process was repeated four times, and finally the filter cake was dried at 100-120 °C for 8-12 h and calcined at 550 °C for 5 h to obtain 42.7 g of titanium dioxide-alumina composite. The structure and performance results of the composite are shown in Table 1.
[0074] [Comparative Example 3] The procedure for preparing the titanium dioxide-alumina composite oxide described in Comparative Example 2 was repeated, except that the calcination temperature after drying was 950°C.
[0075] The results of scanning electron microscope and XRD tests showed that the composite oxides prepared in Comparative Examples 1 to 3 did not have a coral bush-like 3D layer structure, and the TiO2 crystal phase in the composite oxides was mainly rutile crystal phase.
[0076] For the supports prepared above, the specific surface area and pore structure of the composite oxides were determined using the N2 adsorption-desorption method.
[0077] [Table 1]
[0078] [Table 2]
[0079] [Catalyst preparation] [Example 7] 156 g of the composite oxide prepared in Example 1 was impregnated with 100 mL of nickel nitrate aqueous solution with a concentration of 24.72 g Ni / 100 mL for 1 h. After filtration, the filter cake was dried at 110 °C for 6 h and calcined at 600 °C for 4 h to obtain Ni / Al2O3-TiO2 catalyst A with a Ni content of 13.68%.
[0080] [Example 8] 180g of the composite oxide prepared in Example 1 was impregnated with 100mL of nickel nitrate aqueous solution having a concentration of 20.0gNi / 100mL for 0.5 hours. After filtration, the filter cake was dried at 110°C for 5 hours and then calcined at 550°C for 5 hours. Then, 100g of the calcined catalyst precursor prepared above was impregnated with 100mL of nickel nitrate aqueous solution having a concentration of 12.24gNi / 100mL for 0.5 hours. After filtration, the filter cake was dried at 110°C for 4 hours and calcined at 550°C for 6 hours to obtain catalyst B of Ni / Al2O3-TiO2 with a Ni content of 19.82%.
[0081] [Example 9] 156 g of the composite oxide prepared in Example 6 was impregnated with 100 mL of nickel nitrate aqueous solution having a concentration of 13.56 g Ni / 100 mL for 1 h. After filtration, the filter cake was dried at 110 °C for 6 h and calcined at 600 °C for 4 h to obtain catalyst C of Ni / Al2O3-TiO2 with Ni content of 8%.
[0082] [Example 10] 180g of the composite oxide prepared in Example 4 was impregnated with 100mL of nickel nitrate aqueous solution having a concentration of 20.0gNi / 100mL for 0.5 hours. After filtration, the filter cake was dried at 110°C for 5 hours and then calcined at 550°C for 5 hours. Next, 100g of the calcined catalyst precursor prepared above was impregnated with 100mL of nickel nitrate aqueous solution having a concentration of 20gNi / 100mL for 0.5 hours. After filtration, the filter cake was dried at 110°C for 4 hours and then calcined at 550°C for 6 hours to obtain catalyst D of Ni / Al2O3-TiO2 with a Ni content of 25%.
[0083] [Example 11] 180g of the composite oxide prepared in Example 2 was impregnated with 100mL of nickel nitrate aqueous solution having a concentration of 20.0gNi / 100mL for 0.5 hours. After filtration, the filter cake was dried at 110°C for 5 hours and then calcined at 550°C for 5 hours. Next, 100g of the calcined catalyst precursor prepared above was impregnated with 100mL of nickel nitrate aqueous solution having a concentration of 12.24gNi / 100mL for 0.5 hours. After filtration, the filter cake was dried at 110°C for 4 hours and calcined at 550°C for 6 hours to obtain catalyst E of Ni / Al2O3-TiO2 with a Ni content of 19.82%.
[0084] [Example 12] 180g of the composite oxide prepared in Example 3 was impregnated with 100mL of nickel nitrate aqueous solution having a concentration of 20.0gNi / 100mL for 0.5 hours. After filtration, the filter cake was dried at 110°C for 5 hours and then calcined at 550°C for 5 hours. Next, 100g of the calcined catalyst precursor prepared above was impregnated with 100mL of nickel nitrate aqueous solution having a concentration of 12.24gNi / 100mL for 0.5 hours. After filtration, the filter cake was dried at 110°C for 4 hours and calcined at 550°C for 6 hours to obtain catalyst F of Ni / Al2O3-TiO2 with a Ni content of 19.82%.
[0085] [Example 13] 156 g of the composite oxide prepared in Example 5 was impregnated with 100 mL of nickel nitrate aqueous solution with a concentration of 24.72 g Ni / 100 mL for 1 h. After filtration, the filter cake was dried at 110 °C for 6 h and calcined at 600 °C for 4 h to obtain Ni / Al2O3-TiO2 catalyst G with a Ni content of 13.68%.
[0086] [Example 14] 100 g of the composite oxide prepared in Example 1 was immersed in 85 mL of an aqueous palladium chloride solution with a palladium content of 0.32 g / 100 mL. After 1.5 hours, the impregnated composite support was filtered off, reduced with 120 mL of an aqueous hydrazine hydrate solution with a concentration of 10 wt% at room temperature for 1 hour, and repeatedly washed with deionized water until the chloride ions were washed out. After draining, the solid was dried at 120 °C for 6 hours and calcined at 480 °C for 4 hours to obtain a Pd / Al2O3-TiO2 catalyst H with a Pd content of 0.3%.
[0087] [Comparative Example 4] 156 g of the composite oxide prepared in Comparative Example 1 was impregnated with 100 mL of nickel nitrate aqueous solution with a concentration of 24.72 g Ni / 100 mL for 1 h. After filtration, the filter cake was dried at 110 °C for 6 h and calcined at 600 °C for 4 h to obtain Ni / Al2O3-TiO2 catalyst I with a Ni content of 13.68%.
[0088] [Comparative Example 5] 156 g of the composite oxide prepared in Comparative Example 2 was impregnated with 100 mL of nickel nitrate aqueous solution having a concentration of 24.72 g Ni / 100 mL for 1 h. After filtration, the filter cake was dried at 110 °C for 6 h and calcined at 600 °C for 4 h to obtain Ni / Al2O3-TiO2 catalyst J with a Ni content of 13.68%.
[0089] [Comparative Example 6] 156 g of the composite oxide prepared in Comparative Example 3 was impregnated with 100 mL of nickel nitrate aqueous solution having a concentration of 24.72 g Ni / 100 mL for 1 h. After filtration, the filter cake was dried at 110 °C for 6 h and calcined at 600 °C for 4 h to obtain catalyst K of Ni / Al2O3-TiO2 with a Ni content of 13.68%.
[0090] [Example 15] This example demonstrated the application of the catalyst in the selective hydrogenation of butadiene extract tail gas.
[0091] The catalysts used in this example were catalysts A to K.
[0092] The raw material used in this example was butadiene extraction tail gas from a certain plant, the composition of which is shown in Table 3.
[0093] [Table 3]
[0094] In this example, a fixed-bed small-scale evaluation apparatus from Tuochuan Scientific Research Equipment Co., Ltd. was used to support 50 mL of catalyst and to carry out selective hydrogenation of butadiene extraction tail gas.
[0095] The reaction conditions included reaction pressure of 0.5-0.7 MPa, hydrogen amount of 1.92 L / h, reactor inlet temperature of 25°C, circulation ratio of 20:1, and raw material feed rate of 25 mL / h.
[0096] Catalysts A to K were evaluated under the same conditions, and the results of hydrogenation to remove alkynes are shown in Table 4.
[0097] [Table 4]
[0098] From the above table, the catalyst provided by the present invention has high conversion rate of vinyl acetylene and high selectivity of 1,3-butadiene. Since the amount of vinyl acetylene in the hydrogenation product can be controlled to be lower, the hydrogenation product can be directly returned to the extraction system to increase the production of butadiene.
[0099] [Example 16] Using the catalyst A prepared in Example 7, a long-term stability experiment was carried out under the same conditions as in Example 15. The stability evaluation experiment data for 1000 hours is shown in Table 5.
[0100] [Table 5]
[0101] From Table 5, it can be seen that the catalyst provided by the present invention has high stability in the selective hydrogenation of butadiene tail gas having a high alkyne content as a raw material. The hydrogenation catalyst of the present invention not only has high selectivity (%) of 1,3-butadiene and high conversion rate (%) of vinylacetylene, but also can maintain high levels of selectivity and conversion rate for a long period of time, making it suitable for long-term operation.
[0102] It should be noted that the above-mentioned embodiments are only used to explain the present invention, but do not limit the present invention. Although the present invention has been described with reference to exemplary embodiments, it should be understood that the terms used herein are descriptive and explanatory, rather than limiting. The present invention may be modified as defined within the scope of the claims of the present invention, and may be modified without departing from the scope and spirit of the present invention. Although the present invention described herein relates to specific methods, materials and embodiments, it is not intended that the present invention be limited to these examples disclosed herein, but rather the present invention extends to all other methods and applications having the same functions.
Claims
1. A composite oxide comprising 60 to 95% by weight of aluminum oxide and 5 to 40% by weight of titanium dioxide, The composite oxide has a specific surface area of X m as measured by the BET method. 2 / g, the average pore diameter as measured by nitrogen adsorption isotherm is expressed as Y nm, the ratio of X to Y is in the range of 5 to 30; In the above composite oxide, titanium dioxide in an anatase crystal phase accounts for 95% by weight to 100% by weight of the total titanium dioxide, X is in the range of 50 to 200, preferably 60 to 180, more preferably 80 to 150, and Y is in the range of 5 to 25 nm, as measured by an X-ray diffraction method.
2. 2. The composite oxide according to claim 1, wherein the pore volume of said composite oxide is expressed as Z mL / g, Z being in the range of 0.3 to 0.5, and the ratio of X to Z being in the range of 220 to 400, preferably 250 to 350.
3. 3. The complex oxide according to claim 1 or 2, having at least one of the following characteristics: X is between 90 and 150; Y is 9 to 20, preferably 12 to 16; At least 85% of the pores have a pore size in the range of 10-20 nm; Z is 0.3 to 0.4; and / or the composite oxide comprises 5% to 21% by weight of titanium dioxide; and The composite oxide has a 3D layered structure resembling a coral bush.
4. (I) dissolving a soluble aluminum source in water to form an aluminum source solution, dissolving a titanium source in an acid solution to form a titanium source solution, and mixing an ammonium salt and an alkali solution to form a mixed alkali solution; (II) (a) adding the titanium source solution and the mixed alkali solution to the aluminum source solution and maintaining the resulting mixed solution at a first pH value for a first period of time; (b) adding an additional amount of the mixed alkali solution to the mixed solution and maintaining the resulting mixed solution at a second pH value for a second period of time; (c) adding an additional amount of the titanium source solution to the mixed solution and maintaining the resulting mixed solution at a third pH value for a third period of time; (III) after step (II)(c), increasing the temperature of the mixed solution and maintaining it at that temperature for a fourth period to obtain a precipitate; and (IV) drying and calcining the precipitate to obtain a composite oxide comprising alumina and titanium dioxide, preferably with washing and filtering prior to drying.
5. In step (II), the first pH value is less than 5, preferably between 3 and 4; The second pH value is greater than 8.5, preferably between 9 and 10; and The method according to claim 4, wherein the third pH value is greater than 7 and less than 9, preferably between 7.5 and 8.
5.
6. 6. The method according to claim 4 or 5, wherein each of the first, second and third periods is between 5 and 20 minutes, preferably between 10 and 15 minutes; and / or the fourth period is between 20 and 60 minutes.
7. In step (II), the operating temperature is between 25° C. and 60° C.; and / or In step (III), the temperature is increased to between 80° C. and 150° C., and / or The method according to any one of claims 4 to 6, wherein in step (IV), the drying temperature is from 110°C to 130°C and / or the calcination temperature is from 800°C to 1000°C.
8. Use of the composite oxide according to any one of claims 1 to 3 or the composite oxide prepared by the method according to any one of claims 4 to 7 as a catalyst support.
9. A hydrogenation catalyst comprising the composite oxide according to any one of claims 1 to 3 or the composite oxide prepared by the method according to any one of claims 4 to 7 and an active component, A hydrogenation catalyst, preferably wherein said active component is nickel, preferably said catalyst has a nickel content of from 8 to 25% by weight, more preferably from 12 to 20% by weight.
10. 10. A process for selective hydrogenation of alkynes, comprising subjecting a distillate oil to selective hydrogenation of alkynes in the presence of the hydrogenation catalyst of claim 9 to increase the production of butadiene, The distillate oil comprises a C4 distillate oil, preferably a high alkyne tail gas produced as a by-product in a butadiene extraction unit; Preferably, in the above process for selective hydrogenation of alkynes, the reaction temperature is 20° C.-40° C., the molar ratio of hydrogen to alkyne is 1:1-2.5:1, the pressure is 0.5 MPa-0.8 MPa, and the circulation ratio is 10:1-30:1.
Citation Information
Patent Citations
Catalyst for selective hydrogenation of petroleum hydrocarbon and preparation method and application thereof
CN101856613A
C4 alkyne selective hydrogenation catalyst and preparation method and application thereof
CN102886262A
Titanium oxide-aluminum oxide compound as well as preparation method and application thereof
CN103721693A
Rolling molding method for spherical titanium-aluminum composite oxide
CN103861660A
Composite oxide carrier, hydrofining catalyst as well as preparation method and application thereof
CN113828289A